IMPLEMENTATION OF THE FAMILY HOPE PROGRAM (PKH) BY CHILDREN'S EDUCATION COMPANIONS FROM BENEFICIARY FAMILIES IN CILUNCAT VILLAGE, CANGKUANG DISTRICT, BANDUNG REGENCY - Dwineu Asiyah, Sherlyna; Irianti, Decky; Rosilawati, Rosilawati (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2025)
This study aims to examine the implementation of the Program Keluarga Harapan (PKH) by facilitators in supporting the education of children from Beneficiary Families (KPM) in Ciluncat Village using a descriptive qualitative method. Data were collected through interviews, observations, and documentation involving 15 informants, including PKH facilitators, school operators, KPM mothers, and beneficiary children. The analysis is based on four aspects of George C. Edward III’s policy implementation theory: communication, resources, disposition, and bureaucracy. The findings indicate that the program implementation has been fairly effective, as shown by active communication, positive facilitator attitudes, and structured operational procedures. However, several challenges remain, including uneven information dissemination, limited facilities and training for facilitators, lack of parental support for children’s education, and slow bureaucratic processes. The needs analysis highlights the importance of improving facilitator capacity, enhancing communication strategies, providing continuous education for parents, and accelerating reporting mechanisms. By optimizing both formal and informal resources, the implementation of PKH in the education sector can be further strengthened to ensure the sustainability of education for children from beneficiary families.